Effects of organic amendments on soil properties and growth characteristics of Melon (Cucumis melo L.) under saline irrigation - Elbashier, Mohammed M.A.; Shao, Yalu; Wang, Liangkai; Chen, Deli; Zhong, Hua (International Journal of Agricultural and Biological Engineering, 2021)
Establishing strategies of organic amendments application to mitigate the adverse effects of saline irrigation are essential for the sustainable agriculture. A two-year pot experiment was conducted using combinations of organic amendments including effective microorganisms (EM), biochar (BC) and digestate (Di) to investigate their effects on soil and melon (Cucumis melo L.) compared with the recommended NPK fertilizer and Control (CK) under two levels of irrigation water salinity (SL0: 0.25 dS/m, SL1: 2.0 dS/m). Results showed combined applications of organic amendments could significantly (p<0.05) increase soil pH and organic matter (OM) compared to NPK and CK. Application of organic amendments containing BC evidently increased the sodium adsorptive capacity (SAC) under saline water solution. The combined application of EM, BC and Di (EM+BC+Di) could significantly (p<0.05) improve soil available water retention under SL0 and SL1 compared with other treatments. Results also showed organic amendments application can significantly (p<0.05) enhance the photosynthetic rate (Pr) and reduce sodium ion (Na+) content in melon leaves. EM+BC+Di could significantly (p<0.05) increase water use efficiency (WUE) and fruit yield of melon under SL0 and SL1 in comparison to other treatments. It proved that EM+BC+Di had a positive effect on soil improvement, melon growth, WUE and fruit yield. Moreover, EM+BC+Di could be used as an alternative strategy for mineral NPK fertilization of melon at reasonable dosages and frequencies under saline irrigation. Keywords: organic amendments, saline irrigation, soil improvement, melon, water use efficiency DOI: 10.25165/j.ijabe.20211405.6607 Citation: Elbashier M M A, Shao Y L, Wang L K, Chen D L, Zhong H. Effects of organic amendments on soil properties and growth characteristics of Melon (Cucumis melo L.) under saline irrigation. Int J Agric & Biol Eng, 2021; 14(5): 123–129.